Experience of valve bronchial block in pulmonary tuberculosis patients with local inflammatory changes of the bronchial tree - S. V. Sklyuev; D. V. Krasnov (Туберкулез и болезни лёгких)
The objective: to study results of bronchial block in pulmonary tuberculosis patients depending on the presence of local infl ammatory changes in their bronchial tree, the frequency and nature of complications in this category of patients.Subjects and Methods. In order to achieve the above objective, in 2018–2019 in Novosibirsk Tuberculosis Research Institute, all patients who had indications for bronchial block were enrolled in the study. 275 tuberculosis patients were divided into 2 groups: Main Group (n=108) consisted of the patients with infl ammatory changes in their bronchial tree, while Comparison Group (n=167) included patients with no such changes. The valve bronchial block was implanted, effi  cacy of treatment and complications that developed were evaluated. Results. Effi  cacy of valve bronchial blocking did not depend on the presence of local infl ammatory changes in the bronchi, so it can be used without waiting for the relief of infl ammatory changes. The profi le of complications in the groups was comparable.